A mixed-method cluster analysis of physical computing and robotics integration in middle-grade math lesson plans - Zha, Shenghua; Jin, Yi; Wheeler, Rebecca; Bosarge, Erin (Computers and education, 2022)
This study analyzed 281 lesson plans collected from the producers’ websites of 12 educational physical computing and robotics (ePCR) devices. We extracted and coded five variables from each lesson. They were ePCR functionality, coding skills, computational thinking skills, math knowledge, and activity design. First, a two-step cluster analysis was administered to find how three ePCR-related knowledge: ePCR functionality, coding skills, and computational thinking skills, were integrated to teach students ePCR technology in middle-grade math lessons. Results showed three types of lesson plans, including lessons to use basic ePCR functionality to teach students lower-level CT skills, lessons to teach students basic to intermediate coding skills, and lessons to use the technology at the advanced level. Next, we applied the Technological Pedagogical Content Knowledge (TPACK) framework and conducted a second two-step cluster analysis to identify how the technology (ePCR technology), content (math knowledge), and pedagogy (activity design) were integrated into those lesson plans. Results suggested ten clusters of lesson plans with distinct features. We summarized those ten lesson clusters into five categories: 1) ePCR technology lessons, 2) transdisciplinary problem-based learning lessons, 3) technology-assisted lessons, 4) lessons without real-world connections, and 5) lessons integrating middle-grade math learning into ePCR projects. Implications for educators and researchers were discussed at the end of the article. •We analyze 281 physical-computing-and-robotics lesson plans in middle-grade math.•We identify three types of technology integration.•We identify five types of integrated lesson plans.•The largest lesson-plan category is math learning in technology creation projects.•Transdisciplinary problem-based learning lessons only count for 5% of lesson plans.